Ingredients and chemical composition of biscuits available in Peshawar and Mardan divisions - Khattak, Muhammad Muzaffar Ali Khan (Agricultural University, Peshawar, 2003)
Data for ingredient formulation and ingredient composition of nineteen types of biscuits; available at 106 randomly selected bakers' shops of Peshawar and Mardan divisions, was collected. Samples of these biscuits, collected from 10% of the 106 randomly selected bakers shops, were analyzed for chemical composition. The caloric values of these biscuits were determined by multiplying the, protein, carbohydrate and fat contents of these biscuits with 4, 4 and 9. The major raw ingredients used for preparation of biscuits were flour, water, sugar, egg, milk and milk products. The minor ingredients, which usually gave name to the biscuit type, were vanilla, peanut. almond, ginger, cinnamon, jam, chocolate The average ingredients composition of biscuits was 44% flour, 23% sugar, 3% milk, 11% fat and 4% egg. The minor ingredients, used for taste and quality development of biscuits were added in trace amounts. The average chemical composition of biscuits was 5.58% protein 28.05% o fat, 0.47% ash, 1.46 fiber % and 57.27% carbohydrates. The average energy content of biscuits was 518 Kcal/100g. In general, the biscuits analyzed were low in protein, high in fat and energy. Obese individuals are advised to use biscuits with care because it will enhance their obesity. It is a good supplementary food for energy malnourished children and adults.